Mechanical properties and morphological characterization of thermoplastic elastomer polypropylene/epoxidised natural rubber filled reclaimed rubber - Zainol, Nur Sharafina (2015)
Thermoplastic elastomers (TPEs) has emerged its importance in engineering products due to combination properties prevailed by its components;vulcanized rubbers and thermoplastic. This research is an effort to explore the potential of polypropylene (PP) when incorporated with epoxidised natural rubber (ENR) and filled with reclaimed rubber (RR). RR has potential to be utilised as fillers in polymeric matrices to improve mechanical properties, to reduce prices as well as to increase sustainability of petroleum based products. The effect of blend ratio (PP:ENR), mixing parameters (rotor speed, temperature and mixing time) and chemical treatment (maleic anhydride grafted polypropylene) towards mechanical properties of PP/ENR blends were first investigated. Dynamic vulcanisation of PP/ENR blends was performed using sulphur system with help of stearic acid and zinc oxide as activators. Design of experiment (DOE) via statistical method was conceived and optimum process parameters were determined based on mechanical properties of thermoplastic elastomer using response surface methodology (RSM). Regresion models for responses were selected from comparison between the actual data and predicted values by the Design Expert 6.0.10 software. The R2 values of more than 0.900 from analysis of variance determined that the models are accurate to represent the actual systems. Then, PP/ENR filled RR blends with/without RR were prepared by melt compounding through an internal mixer, Haake Rheomix at temperature and rotor speed of 170ºC and 60 rpm and followed by compression molding using hot press. Reclaimed rubber of composition 10, 20, 30, 40 or 50 percentage was introduced during the blending process. The characteristics and mechanical properties of the blends with or without RR had been determined using tensile test, Izod impact test and hardness test on compression molded specimens. The properties were further analysed and supported with swell measurements, Fourier Transform infrared spectroscopy, differential scanning electron calorimetry and scanning electron microscopy (SEM). The PP/ENR filled with 30% RR showed optimum result in flexibility for elongation at break (Eb) and impact strength of 18.5% and 33 J/m, respectively with minimum reduction in tensile strength of only 23%. The observed microstructure of specimens via SEM showed good miscibility between rubber and plastic due to uniform dispersion of rubber components, ENR and RR in PP matrices. The Eb and impact strength were observed to increase with increasing of RR content due to significant interaction between the materials. Through optimisation of formulation of PP/ENR filled RR constituents and compatibilisation techniques, a green material with improved toughness and flexibility with significant tensile and impact properties compared to PP is achieved. This new material has potential as green alternative for existing PP based product.